STRUCTURAL AND FUNCTIONAL CHANGES IN CENTRAL HEMODYNAMICS AND ASSESSMENT OF THE EFFECTIVENESS OF ANTIHYPERTENSIVE THERAPY IN PREGNANT WOMEN WITH HYPERTENSION - Kamolova Diyora Jamshedovna; Sunnatullayev Diyorbek (World Scientific Research Journal, 2025)
Abstract: This study examines the changes in central hemodynamics in pregnant women with hypertension and evaluates the effectiveness of antihypertensive therapy. The research was conducted at the clinic of Samara State Medical University, where an echocardiographic analysis of the cardiovascular system was performed on 88 pregnant women. The data obtained allow for the identification of structural and functional changes in central hemodynamics in patients with hypertension and provide recommendations for optimizing antihypertensive therapy.